DETERMINAN STRUKTUR PASAR TENAGA KERJA SEKTOR TRANSPORTASI DI INDONESIA - Wahyu Widodo Rodhiyawan (STIE Mahardhika, 2022)
The development of the digital economy has resulted in the loss of some jobs, the emergence of new jobs, and the possibility of labor shifting between the two. This raises the potential for labor that is not absorbed which of course will cause unemployment problems. With the COVID-19 pandemic, which requires Large-Scale Restrictions (PSBB) which of course affects the transportation sector. This study aims to examine the influence of the digital economy, investment, the COVID-19 pandemic, and the Job Creation Act on the labor market structure of the transportation sector in Indonesia. The research method used is quantitative. The data used is a time series from January 2018 to November 2020. The results of this study indicate that the digital economy has no effect on the labor market structure of the transportation sector in Indonesia. Meanwhile, investment, the COVID-19 pandemic, and the Job Creation Act also each have a significant effect on the labor market structure of the transportation sector in Indonesia. The impact of investment and the COVID-19 pandemic on the labor market structure of the transportation sector in Indonesia is negative. Meanwhile, the effect of the Job Creation Act on the labor market structure of the transportation sector in Indonesia is positive. Simultaneously, the digital economy, investment, the COVID-19 pandemic, and the Job Creation Act affect the labor market structure of the transportation sector in Indonesia.